2021
DOI: 10.18488/journal.1.2021.113.177.187
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers Conceptual Understanding in Space Science

Abstract: Contribution/ Originality: This study is one of the very few studies which have investigated the conceptual understanding of preservice teachers in space science. The findings of the study reveal the needs to integrate more relevant and updated instructional strategies into the classroom to shed light on the misconceptions held by future teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Another study by Felicita (2021) on seventh grade students at Hyderabad, India, reported that many students understand very limited concepts about the phases of Moon and seasons. Ibrahim et al (2021) also reported that pre-service teachers in a public Malaysian university have moderately (37.86%) conceptual understanding on space science with a number of misconceptions in basic astronomy.…”
Section: Introductionmentioning
confidence: 94%
“…Another study by Felicita (2021) on seventh grade students at Hyderabad, India, reported that many students understand very limited concepts about the phases of Moon and seasons. Ibrahim et al (2021) also reported that pre-service teachers in a public Malaysian university have moderately (37.86%) conceptual understanding on space science with a number of misconceptions in basic astronomy.…”
Section: Introductionmentioning
confidence: 94%
“…Yapılan çalışmalara bakıldığında, çocuklara ilişkin uzay ve astronomi ile ilgili çalışmaların oldukça sınırlı olduğu görülmektedir (Vosniadou ve Brewer,1992;Brewer, 2008;Türk, 2018;DeWitt ve Bultitude, 2020;Güçhan-Özgül, Akman, ve Saçkes, 2018). Bunun yanı sıra, öğretmen adaylarına yönelik (İbrahim, Yusof, Zulkipli, ve Dalim, 2021;İyibil ve Sağlam-Arslan, 2010;Emrahoğlu ve Öztürk, 2009) ve uzay bilimine yönelik tutumlarla ilgili (Schreiner ve Sjoberg, 2004) yapılan çalışmalarda literatürde mevcuttur. Astronomi konusundaki çalışmalarda ise, dünyanın en büyük astronomi topluluğu olan "The International Astronomical Union" (IAU-Uluslararası Astronomi Birliği) toplantılarında 1988'den 2006'ya kadar sunulan tam metin bildirilerin, Bretones ve Nego (2011) tarafından analiz edildiği bir çalışmada dikkat çekici bir sonuç olarak, astronomi eğitimi ile ilgili en az sayıda araştırmanın okul öncesi ve ilkokul döneminde gerçekleştirildiği görülmüştür.…”
Section: Introductionunclassified